The Concept of Using Art Criticism Activities in the Visual Arts Subject Group to Enhance Thinking Ability of Basic Education Learners - Phoungmanee, Thairoj; Chaikularb, Isariyaporn; Jareansuk, Kotchasri (Academic Innovation Journal, 2026)
This academic article aimed to study the use of art criticism activities in the visual arts subject group to enhance the cognitive potential of learners at the basic education level by implementing art instructional management, art criticism, and cognition as frameworks for content analysis. The findings revealed that art criticism was a concept proposed by scholars who believed that learning the value of artworks could be fostered through a four-step process: description, analysis, interpretation, and Evaluation. In implementing art criticism activities, considerations should be given to the learners' grade level, class time, and their readiness, with instructional strategies that teachers can use as guidelines for planning, including: 1) organizing visual discussions and multi-directional thinking, 2) managing learning that encourages reflective thinking through self-reflection, and 3) managing learning through simulated situations. These strategies were then employed to plan objectives, content, activities, teaching methods, instructional media, and assessment ultimately. The results showed that art criticism activities enhanced learners' cognitive potential.